Effect of three dose of organic matter with the inoculation of soil improvement microorganisms in the performance of quinua culture (Chenopodium quinoaWill.), variedad Pasankalla, in populated center of Huanchac, Independencia - Ancash (Aporte Santiaguino, 2020)
The present investigation the objective was to evaluate the effect of three doses of organic matter with the inoculation of soil-enhancing microorganisms on the yield of the quinoa (ChenopodiumquinoaWill.) Crop, Pasankalla variety, the optimal dose of organic matter, the performance and economic analysis. Randomized Complete Blocks design with four blocks and five treatments was used (T0 =Witness, T1 = 10 Tn / ha of MO + Microorganisms, T2 = 20 Tn / ha of MO + Microorganisms, T3 = 30 Tn / ha of MO + Microorganisms and T4 = 158 N -109 P2O5-117 K2O Kg / ha). The parameters of germination percentage, plant height, stem diameter, panicle induction, biomass, weight of 1000 grains, yield and economic analysis were evaluated. In conclusion, it was found that applying 20 Tn / ha of M.O. + Microorganism (300 g / ha ofTricho-D + 1 L / ha of Bacthon), 64; 48 %profitabilitywas obtained, with a cost benefit of 1; 82 soles and the control being the one with the lowest profitability, 12; 50 % and a lower cost benefit of 0; 10 soles .